Highly Resistant LaCo1−xFexO3 Perovskites Used in Chlorobenzene Catalytic Combustion - Acosta Perez, Hector (2023)
The stability of LaCo1−xFexO3 perovskite structures (x = 0; 0.25; 0.5; 0.75; 1) was studied in the combustion of chlorobenzene. This family of catalysts was synthesized by the citrate method obtaining pure structures. The Fe doping in the original structure induces electronic environments capable of generating the Co2+/Co3+ redox couple. The characteristics observed in bulk are perfectly reflected on the surface, favoring a high resistance of the solids to chlorine poisoning. Superior stability under reaction conditions was observed in the phase with the lowest Fe content (x = 0.25), remaining stable at 100% combustion of chlorobenzene during 100 h, not observing intermediate reaction products. These results open up a new avenue for designing and fabricating high-performance catalysts in the environmental field.